2018
DOI: 10.1021/acscentsci.8b00042
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Catalytically Relevant Edge Electronic States of MoS2

Abstract: Molybdenum disulfide (MoS2) is a semiconducting transition metal dichalcogenide that is known to be a catalyst for both the hydrogen evolution reaction (HER) as well as for hydro-desulfurization (HDS) of sulfur-rich hydrocarbon fuels. Specifically, the edges of MoS2 nanostructures are known to be far more catalytically active as compared to unmodified basal planes. However, in the absence of the precise details of the geometric and electronic structure of the active catalytic sites, a rational means of modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 60 publications
4
53
0
Order By: Relevance
“…17 These one-dimensional states were first predicted by M. Bollinger et al 219 and later visualised using scanning tunnelling microscopy 219 and scanning transmission X-ray microscopy. 220 The thermochemistry predictions were verified by T. Jaramillo et al by measuring the catalytic activity of UHV sputtered MoS 2 nanoislands of various sizes. 17 The observed correlation between the rate of hydrogen evolution and the fraction of edge sites of MoS 2 nanoparticles unambiguously suggests that in the case of semiconducting 2H MoS 2 nanostructures, the electrocatalytic HER predominantly takes place at the edge sites.…”
Section: How Stable the Metastable 1t(1t 0 ) Phases Are?mentioning
confidence: 78%
“…17 These one-dimensional states were first predicted by M. Bollinger et al 219 and later visualised using scanning tunnelling microscopy 219 and scanning transmission X-ray microscopy. 220 The thermochemistry predictions were verified by T. Jaramillo et al by measuring the catalytic activity of UHV sputtered MoS 2 nanoislands of various sizes. 17 The observed correlation between the rate of hydrogen evolution and the fraction of edge sites of MoS 2 nanoparticles unambiguously suggests that in the case of semiconducting 2H MoS 2 nanostructures, the electrocatalytic HER predominantly takes place at the edge sites.…”
Section: How Stable the Metastable 1t(1t 0 ) Phases Are?mentioning
confidence: 78%
“…Developing nonprecious metal catalysts with increased activity and durability is crucial to advance solid‐state electrocatalysis for sustainable energy technologies that mainly rely on precious metals such as platinum (Pt), palladium (Pd), and silver (Ag) . Recently, 2D nanomaterials such as molybdenum disulfide (MoS 2 ) and carbide (Mo 2 C) have been identified as promising candidates to replace precious metal catalysts owing to the unique electronic properties of their edge structures . However, the basal plane of these catalysts containing substantial amount of their surface structure remains nearly inactive making these catalysts inefficient, especially for practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the H passivation of the zigzag (MoS2)3/ (WS2)3 nanoribbon does not make the system semiconducting. Both the symmetric and asymmetric armchair nanoribbons may lower their energy via formation of corrugation [33] or the bond reconstruction mechanism, as is widely realized for semiconductor surfaces, particularly the (001) surface of diamond structure materials and the (110) surface of zincblende materials [54]. However, in this work we have not considered any possible reconstructions of geometries discussed in the text.…”
Section: Zigzag (Mos2)3/ (Ws2)3 Lateral Nanoribbonsmentioning
confidence: 99%
“…Previous research shows MoS 2 , WS 2 , MoSe 2 , WSe 2 zigzag nanoribbons as metallic and ferromagnetic and the armchair nanoribbons as semiconducting [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The edges of MoS 2 nanostructures are known to be very catalytically active [ 33 ]. Parija et al demonstrated that edge corrugations yield distinctive spectroscopic signatures using first-principles calculations, X-ray absorption spectroscopy, scanning transmission X-ray microscopy (STXM) imaging [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation